All systems go! energy systems of the body - Leigh, Richard; Gazzo, Klaire; Gelvin, Kim
This DVD explains anaerobic and aerobic glycolysis, how myosin and actin use ATP to contract muscles, oxygen uptake and oxygen deficit, the interplay of the three energy systems, chronic & acute training effects and much more, with regular breaks for note-taking and discussion.